Tular Nalar: Upaya Melahirkan Lingkar Epistemik Literasi Digital - Finsensius Yuli Purnama; Adven Sarbani (Jurnal Riset Jurnalistik dan Media Digital, 2023)
Abstract. Traditional intellectuals only focus on theory and never place their investigations as an effort to solve existing social problems. On the other hand, the link between academic activities that answer problems and engage in concrete issues in society will foster what is known as organic intellectuals. Abstrak. Intelektual tradisional hanya berkutat pada teori dan tidak pernah menempatkan penyelidikannya sebagai upaya menyelesaikan persoalan sosial yang ada. Di lain pihak, keterkaitan kegiatan akademik yang menjawab persoalan dan terlibat dalam isu-isu konkret dalam masyarakat akan menumbuhkan apa yang disebut sebagai intelektual organik.